2022
DOI: 10.3390/molecules27123714
|View full text |Cite
|
Sign up to set email alerts
|

Dihydrotanshinone I Enhances Cell Adhesion and Inhibits Cell Migration in Osteosarcoma U−2 OS Cells through CD44 and Chemokine Signaling

Abstract: In the screening of novel natural products against cancer using an in vitro cancer cell model, we recently found that tanshinones from a traditional Chinese medicine, the rhizome of Salvia miltiorrhiza Bunge (Danshen), had potent effects on cell proliferation and migration. Especially for human osteosarcoma U−2 OS cells, tanshinones significantly enhanced the cell adherence, implying a possible role in cell adhesion and cell migration inhibition. In this work, therefore, we aimed to provide a new insight into … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 72 publications
0
5
0
Order By: Relevance
“…In OS and ONFH, the regulation of cell adhesion may affect the metastatic ability of tumor cells and structure and function of bone tissue [ 34 ]. T cells, a key cell type in the immune system, participate in regulating immune responses and immune tolerance [ [35] , [36] , [37] , [38] , [39] ]. The abnormal differentiation of T cells may be associated with immune imbalance and inflammatory responses in OS and ONFH [ 36 ].…”
Section: Discussionmentioning
confidence: 99%
“…In OS and ONFH, the regulation of cell adhesion may affect the metastatic ability of tumor cells and structure and function of bone tissue [ 34 ]. T cells, a key cell type in the immune system, participate in regulating immune responses and immune tolerance [ [35] , [36] , [37] , [38] , [39] ]. The abnormal differentiation of T cells may be associated with immune imbalance and inflammatory responses in OS and ONFH [ 36 ].…”
Section: Discussionmentioning
confidence: 99%
“…Zheng et al identified POGZ as a hub gene in osteosarcoma, related to the cell cycle pathway 33 . Fan et al found that dihydrotanshinone I could regulate osteosarcoma U-2 OS cells' adhesion and migration via chemokine pathways 34 . As for the JAK STAT pathway, Lv et al utilized bioinformatics analyses and firstly www.nature.com/scientificreports/ mined serglycin as a prognostic marker involved with the JAK/STAT pathway 35 .…”
Section: Discussionmentioning
confidence: 99%
“…A number of studies have also highlighted the effect of CD44 on AKT in relation to cancer cell growth, motility, invasion and stemness. 217 , 218 , 219 Thanee et al. 220 found that silencing CD44 inhibited cholangiocarcinoma progression and aggressiveness, as well as AKT and mTOR phosphorylation.…”
Section: Cancer‐associated Pathways Regulated By Cd44mentioning
confidence: 99%
“…A number of studies have also highlighted the effect of CD44 on AKT in relation to cancer cell growth, motility, invasion and stemness. [217][218][219] Thanee et al 220 found that silencing CD44 inhibited cholangiocarcinoma progression and aggressiveness, as well as AKT and mTOR phosphorylation. As demonstrated by GC cell lines and an experimental animal model, chitinase-like protein CHI3L1 binding to CD44v3 was a specific inducer of activation of ERK, AKT, and β-catenin signaling and enhancement of GC transfer.…”
Section: Pi3k-akt Signaling Pathwaymentioning
confidence: 99%
See 1 more Smart Citation